ANALISIS PENDAPATAN DAN KELAYAKAN USAHA BUDIDAYA IKAN AIR TAWAR DENGAN POLA KERAMBA JARING APUNG (KJA) DI KECAMATAN WARKUK RANAU SELATAN KABUPATEN OKU SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2015)
This research aims to analysed the incoming and the feasibility study of unsalted fishery in KJA at South Warkuk Ranau District of South OKU Region. The research done with purposive method, and the research method used case study method. Simple random sampling as the sample method, taken 24 samples of 52 samples of South Warkuk Ranau. The research done in Ranau Lake of South OKU District where it was the farmers usually depent on their lives from the coffee plant. The result shown that the incoming from this business (unsalted fishery) was 8.906.582 million rupiah in a month and the feasibility study shown that this unsalted fishery had R/C 3,07 so with that value, it was very feasible for farmers to go on this fishery.